2015
DOI: 10.1002/jobm.201500291
|View full text |Cite
|
Sign up to set email alerts
|

High‐level iron mitigates fusaricidin‐induced membrane damage and reduces membrane fluidity leading to enhanced drug resistance in Bacillus subtilis

Abstract: Fusaricidins are a class of cyclic lipopeptide antibiotics that have strong antifungal activities against plant pathogenic fungi and excellent bactericidal activities against Gram-positive bacteria. The mechanism through which fusaricidin exerts its action is not yet entirely clear. To investigate the mode of action of fusaricidin, we determined the physiological and transcriptional responses of Bacillus subtilis to fusaricidin treatment by using a systems-level approach. Our data show that fusaricidin rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Iron is a key nutrient for bacterial growth, further the Gram-negative strains were dependent on the TonB-dependent transporters for their iron uptake process . Moreover, the previous study revealed that a high concentration of iron can reduce the damage of fusaricidin to the cell membrane and increase the drug resistance in Bacillus subtilis . Furthermore, the iron plays a significant role in the development of Pseudomonas aeruginosa biofilms, which also makes the strain resistant to antibiotics .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron is a key nutrient for bacterial growth, further the Gram-negative strains were dependent on the TonB-dependent transporters for their iron uptake process . Moreover, the previous study revealed that a high concentration of iron can reduce the damage of fusaricidin to the cell membrane and increase the drug resistance in Bacillus subtilis . Furthermore, the iron plays a significant role in the development of Pseudomonas aeruginosa biofilms, which also makes the strain resistant to antibiotics .…”
Section: Resultsmentioning
confidence: 99%
“…36 Moreover, the previous study revealed that a high concentration of iron can reduce the damage of fusaricidin to the cell membrane and increase the drug resistance in Bacillus subtilis. 37 Furthermore, the iron plays a significant role in the development of Pseudomonas aeruginosa biofilms, which also makes the strain resistant to antibiotics. 38 Therefore, the increased level of expression in iron-related proteins of bacteria can enhance the iron uptake and enhance bacterial resistance to antibiotics.…”
Section: Functional Analysis Of Differentially Expressed Proteins In ...mentioning
confidence: 99%
“…Additionally, after 3 h, the genes involved in cell wall modification, general stress responses, fatty acid and amino acid catabolism, and cation transport were found to be upregulated, while glucose and gluconeogenesis genes were repressed. The same group recently demonstrated that the bactericidal activity of fusaricidin C coincided with an increased production of free hydroxyl radicals (51). Although a greater emphasis has been placed on membrane damage, it is also possible that fusaricidins inhibit intracellular targets.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the impact of dye interaction on green emissions is an additional measure of viability alongside red fluorescence intensity from PI only stained cells and the ADR. The literature pertaining to application of the BacLight Kit to assess bacterial viability has only used the green:red fluorescence ratio as a measure of the proportion of viable cells [ 17 , 39 , 45 , 46 , 47 , 48 ]. The work presented here uses the approach outlined in our previous publication [ 42 ] .…”
Section: Introductionmentioning
confidence: 99%